Can common dietary assessment methods be better designed to capture the nutritional contribution of neglected, forest, and wild foods to diets? - Raneri, Jessica E.; Boedecker, Julia; Fallas Conejo, Diego A.; Muir, Giulia; Hanley-Cook, Giles; Lachat, Carl (Frontiers in Nutrition, 2023)
Food systems are the primary cause of biodiversity loss globally. Biodiversity and specifically, the role that wild, forest and neglected and underutilised species (NUS) foods might play in diet quality is gaining increased attention. The narrow focus on producing affordable staples for dietary energy has contributed to largely homogenous and unhealthy diets. To date, evidence to quantify the nutritional contribution of these biodiverse foods is limited. A scoping review was conducted to document the methods used to quantify the contribution of wild, forest and NUS foods. We found 37 relevant articles from 22 different countries, mainly from Africa (45%), the Americas (19%) and Asia (10%). There were 114 different classifications used for the foods, 73% of these were specifically related to wild or forest foods. Most dietary assessments were completed using a single day qualitative or quantitative 24-hour open recall (n=23), or a food frequency questionnaire (n=12). There were 18 different diet related indicators used, mainly nutrient adequacy (n=9) and dietary diversity scores (n=9). Often, no specific nutritionally validated diet metric was used. There were 16 studies that presented results (semi)quantitatively to measure the contribution of wild, forest or NUS foods to dietary intakes. Of these, 38% were aggregated together with broader classifications of ‘traditional’ or ‘local’ foods, without definitions provided meaning it was not possible to determine if or to what extend wild, forest of NUS foods were included (or not). In almost all studies there was insufficient detail on the magnitude of the associations between wild, forest or NUS foods and dietary energy or nutrient intakes or the (qualitative) diet recall methodologies that were used inhibited the quantification of the contribution of these foods to diets. A set of six recommendations are put forward to strengthen the evidence on the contribution of wild, NUS and forest foods to human diets.